PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI PERISTIWA ALAM TEMA 8 SUB TEMA 1 PEMBELAJARAN 1 KELAS 1 SD - Ayu Saputri, Nindi; Antika Putri, Oktya; Elvadola, Connyta (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
Learning media is a part that really determines the effectiveness and reduces the limits of learning objectives. This research is a qualitative descriptive study with the title SD Learning Multimedia Development on Natural Events Material Theme 8 Sub-theme 1 Learning 1 Class 1 SD. The object of this research is how the Development of Elementary School Learning Multimedia in Material Natural Events Theme 8 Sub-theme 1 Learning 1 Class 1 SD. The data technique in this research uses the method of observation, documentation, and interviews. This learning media is also made so that students do not get bored when studying at home with their parents. Multimedia-based learning media is a learning media that uses the combination of images, sound or audio and video.